Lung cancer molecular mutations and abnormal glycosylation as biomarkers for early diagnosis. (2021) - Yang, Shuang; Xia, Jun; Yang, Zeren; Xu, Mingming; Li, Shuwei
Highlight: Mutations in oncogenic drivers are associated with the progression and metastasis of lung adenocarcinoma Abnormal glycosylation defines the malignancy of lung cancer Circulating glycoproteins in the blood may be potential biomarkers of tumor development and progression Inhibition of signal transduction during tumor development may reverse abnormal glycosylation Abstract: Lung cancer is the leading cause of mortality and morbidity in tumor-related deaths in the world. Early detection of tumors can greatly improve the survival rate of patients. However, the lack of reliable blood biomarkers remains a major challenge for early diagnosis. The blood proteins secreted by the lung bronchi and bronchial arteries may have characteristic glycosylation patterns associated with tumors, which are different from normal physiological and pathological conditions. In this review, we outline the oncogenic drivers, signaling pathways related to KRAS, gene and protein mutations, and oncogenic regulation of protein glycosylation. Based on to the TCGA transcriptomics and antibody-based proteomics data, we discussed oncogene and glycoproteins detected in the blood as tumor biomarkers. We hypothesize that glycoproteins whose glycosylation can be reversed by targeted drugs may serve as potential tumor biomarkers.